2021
DOI: 10.1101/2021.08.02.21261481
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep Learning of Left Atrial Structure and Function Provides Link to Atrial Fibrillation Risk

Abstract: Aims: Increased left atrial (LA) volume is a known risk factor for atrial fibrillation (AF). There is also emerging evidence that alterations in LA function due to an atrial cardiomyopathy are associated with an increased risk of AF. The availability of large-scale cardiac MRI data paired with genetic data provides a unique opportunity to assess the joint genetic contributions of LA structure and function to AF risk. Methods and results: We developed deep learning models to measure LA traits from cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…To explore whether the risk for stroke of undetermined source can be partially explained by established stroke etiologies, we explored in MR analyses whether genetic predisposition to carotid atherosclerosis (proxied by common carotid artery intima media thickness [cIMT] in 71,128 individuals of European ancestry from the CHARGE Consortium 27 ), a main cause of LAAS, to atrial fibrillation (65,446 cases, 522,744 controls from a trans‐ethnic meta‐analysis of the AFGen Consortium, the UK Biobank, the Broad AF Study, and the Biobank Japan 28 ), the primary source of CES, and to cerebral small vessel disease (proxied by white matter hyperintensities [WMHs] volume in 42,310 individuals in the UK Biobank 29 ), the main cause of SVS, is associated with stroke of undetermined source in the SiGN data. As a less established cause of cardioembolism, we also explored associations with genetically predicted left atrial structural traits, 30 as derived from deep learning algorithms in cardiac magnetic resonance imaging (MRI) data (40,558 individuals from the UK Biobank 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…To explore whether the risk for stroke of undetermined source can be partially explained by established stroke etiologies, we explored in MR analyses whether genetic predisposition to carotid atherosclerosis (proxied by common carotid artery intima media thickness [cIMT] in 71,128 individuals of European ancestry from the CHARGE Consortium 27 ), a main cause of LAAS, to atrial fibrillation (65,446 cases, 522,744 controls from a trans‐ethnic meta‐analysis of the AFGen Consortium, the UK Biobank, the Broad AF Study, and the Biobank Japan 28 ), the primary source of CES, and to cerebral small vessel disease (proxied by white matter hyperintensities [WMHs] volume in 42,310 individuals in the UK Biobank 29 ), the main cause of SVS, is associated with stroke of undetermined source in the SiGN data. As a less established cause of cardioembolism, we also explored associations with genetically predicted left atrial structural traits, 30 as derived from deep learning algorithms in cardiac magnetic resonance imaging (MRI) data (40,558 individuals from the UK Biobank 31 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have used large databases of healthy individuals to investigate genetic variants that are associated with natural variation in LA structure and function in healthy populations. [6][7][8] These studies have identified genome-wide significant loci near genes that affect myocyte development and contractile function 8 and overlap with known regulators of variation in left ventricular and right ventricular structure and function in healthy individuals. 28,30 Our study differs from these previous studies by examining genetic variation in a clinical, disease-penetrant population of patients receiving care in a tertiary care center.…”
Section: Discussionmentioning
confidence: 99%
“…All voltages were transformed to millivolts, and all MRI values were normalized to have mean 0 and standard deviation 1 for each individual. The MRIs were cropped to the smallest bounding box which contained all cardiac tissues in all 50 frames as determined by the semantic segmentation in [52].…”
Section: Methodsmentioning
confidence: 99%